Effect of topical atenolol on intraocular pressure. - Wettrell, K. (1977)
Placebo and topical atenolol (Tenormin), a selective beta1-adrenergic blocking substance with no intrinsic sympathomimetic or membrane-stabilising properties, were tested in 16 patients with ocular hypertension in a double-blind cross-over trial. Three different concentrations of atenolol (1, 2, and 4%) were investigated. After a single instillation there was a statistically significant fall in mean intraocular pressure (IOP) with all the concentrations after one hour, with a maximum after two to three hours. The effect had passed off after seven hours. In multiple-dose studies with applications three times a day for seven days there was a statistically significant fall in the mean IOP on the first day of treatment (all three concentrations), which persisted throughout the week. In the single-dose study only a slight dose-dependence was observed. This could not be confirmed in the multiple-dose trial. Pupil size, corneal sensitivity, systemic blood pressure, and heart rate were unaffected. No side effects were noted. Thus topically applied atenolol lowers IOP in patients with ocular hypertension and may be clinically useful.